Inclusión de harina de tagua (Phytelephas aequatorialis) en dietas de gallinas Hy-Line sobre parámetros productivos en la fase de postura - Vera Chávez, Oscar Octavio (2021)
With the objective of evaluating the inclusion of tagua flour at two inclusion levels (2% and 4%) in two rearing densities (D4: 4 / birds / m2 and D5: 5 / birds / m2) in Hy-Lyne breed hens. On productive parameters in the laying phase, an investigation was carried out at the Adelaida poultry farm of Chone canton with 441 birds distributed in three treatments and seven repetitions organized in a completely random design, where the productive variables (live weight, feed consumption, conversion, egg production) and economic matter (cost of production per eggs, gross and net income). There were no statistically significant differences in live weight (p> 0.05) for densities and inclusion levels, food consumption did not vary, however, in week one and four there was higher consumption 102, 43 and 110, 3 grams in D5, the egg production (%) was higher in D4 in relation to D5 with values between 69.20% to 73.07% respectively, the eggs produced per bird were observed higher number of eggs (37) in the level of inclusion at 2% tagua flour in week five, the cost of egg production was lower in birds fed 2% tagua flour in diets ($ 0.04) for both densities. It is concluded that the addition of tagua flour does not influence the productive indicators and the economic analysis was favorable because the cost of egg production with different treatments was between $ 0.04 and $ 0.05 cents during the evaluated period.